Acute lumbar disk injuries in active patients - Lively, M. W.; Bailes, J. E. (The Physician and Sportsmedicine, 2005)
Managing acute lumbar disk herniations in active patients can be challenging for physicians, especially when controversies surrounding treatment options make choosing the right care more difficult. The prognosis for lumbar disk herniations is generally favorable, and most patients will improve with conservative measures, such as early activity and avoiding bed rest. Minimally invasive techniques, such as percutaneous diskectomy, laser diskectomy, and epidural corticosteroid injection, may help control sciatic pain. Athletes who sustain late-season disk injuries should receive conservative treatment before considering surgery. Those who have early-season injuries may be able to return to competition sooner by having a microdiskectomy before a full course of conservative therapy is completed, but data supporting this approach are currently lacking.